Complementary and alternative medicine use in patients with mental disorders in Turkey - ÖZTÜRK, AHMET; BAHÇECİ, Bulent; Bagcioglu, Erman; Ozturk, AHMET; Bulbul, Feridun; ŞAHİNER, Ismail Volkan; Tuncer, Buket Eryonucu; Guzel, Halil Ibrahim; HOCAOĞLU, Cicek (My University, 2013)
Purpose: The aim of this study was to determine the prevalence of complementary and alternative medicine (CAM) use and the associated socio-demographic factors among patients with mental disorders in the Turkish community.